Hearing Vocabulary as a Key Element for Image Creation in the Original Text and Its Translation (Based on the Short Story Butterfly’s Tongue by Manuel Rivas) - KONDRATENKO, Oleksandra (Linguistic and Conceptual Worldviews, 2022)
The paper sets out to provide a comprehensive description of the problem of reproducing the hearing vocabulary in the Ukrainian translation as it plays a key role in the image creation. The research is based on the data collected from the short story La lengua de las mariposas written by modern Spanish novelist Manuel Rivas since it's been noted that this kind of lexis is used actively to describe, on one hand, the special atmosphere that was reigning in Spain at that time and, on the other hand, to specify the speech portrait of the characters. According to the results of the analysis, the main challenges in translation were identified. These are the physical sound description, visual images based on metaphors and epithets, phonetic peculiarities and euresemy cases. We have found out that when the verbal image with a hearing component is traced on the denotative meaning (that is to say, used to represent language world picture), there is no problem in establishing the direct correspondence between two languages. The major problems in reproducing this type of lexis are faced when it comprises such functional, stylistics connotations and associative features that differ from those that exist in the target language. Then the in-depth semantic structure analysis is needed that will determine the special translation transformations, for example the use of functional correspondence or neutralization of the figure. Furthermore, the background knowledge of the recipient must be considered as the sound terms may contain additional implicit information as well. But one should always be aware of the possible stylistic losses that may be a result of this or that transformation. The awareness of it will ensure the content unity of the text that is being translated.
Keywords: literary translation, hearing vocabulary, sound terms, verbal image connotation, stylistics